Effect of Motivation and Work Experience on Employee Performance at PT. Perkasa Sakti in Cimone - Muhammad Ramdhan (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
This study aims to determine the effect of motivation and work experience on employee performance at PT. Perkasa Sakti in Cimone. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The result of this research is that motivation has a significant effect on employee performance by 45.1%, hypothesis testing is obtained t count > t table or (7.306 > 1.997). Work experience significantly affects employee performance by 49.9%; hypothesis testing is obtained t count > t table or (8.041 > 1.997). Motivation and work experience simultaneously significantly affect employee performance with the regression equation Y = 9.701 + 0.326X1 + 0.441X2. The influence contribution is 63.2%, hypothesis testing is obtained by F arithmetic > F table or (54.954 > 2.750).